DESIGN OF AN ANDROID-BASED ONLINE REGISTRATION APPLICATION FOR OUTPATIENT SERVICE AT THE NUR ILAHI MENTAL HEALTH CLINIC: ANDROID-BASED ONLINE REGISTRATION APPLICATION - Rachmawati, Ghaida Fauziyyah; Abdussalaam, Falaah; Setiatin, Sali (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Nur Ilahi Mental Health Clinic is a health care facility that has implemented service digitization. Currently, patient who are registered as health insurance (JKN) participants can register online through the Mobile JKN application provided by BPJS Health. This condition creates inequality in the queuing service experience of general patients an BPJS patients, especially in terms certainty of queue numbers and estimated service time received. Based on these problems, this study aims to design an android-based outpatient registration application that is easy to use by general patients (Non-BPJS). Methods: The research method used in this research in the prototyping method which is a software method in the form of a physical model directly involving the creation of an initial model of the software to feedback before final development begins. Results: The results showed a percentage of 100% on ease of use as well as satisfaction and availability of using the application. With the design of this android-based general patient registration application, it is hoped that it will be able to provide solutions to patients who do not have BPJS insurance to register for queues online. Conclusion: So that there is no gap between BPJS patient and Non-BPJS patients in registering at the Nur Ilahi Mental Clinic.